2022
DOI: 10.3389/fped.2022.735335
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Years Lived With Disability, and Time Trends for 16 Causes of Blindness and Vision Impairment: Findings Highlight Retinopathy of Prematurity

Abstract: BackgroundCause-specific prevalence data of vision loss and blindness is fundamental for making public health policies and is essential for prioritizing scientific advances and industry research.MethodsCause-specific vision loss data from the Global Health Data Exchange was used. The burden of vision loss was measured by prevalence and years lived with disability (YLDs).FindingsIn 2019, uncorrected refractory error and cataract were the most common causes for vision loss and blindness globally. Women have high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Globally, the YLD numbers of blindness, SVL, and MVL showed a rising trend for both men and women. As reported in Zhang et al, the prevalence of blindness, SVL, and MVL due to neonatal disorders increased by 33.53 and 13.73%, respectively, from 1990 to 2019 (22). The NPB-related eye diseases include congenital cataracts, ROP, congenital glaucoma, refractive error, etc.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Globally, the YLD numbers of blindness, SVL, and MVL showed a rising trend for both men and women. As reported in Zhang et al, the prevalence of blindness, SVL, and MVL due to neonatal disorders increased by 33.53 and 13.73%, respectively, from 1990 to 2019 (22). The NPB-related eye diseases include congenital cataracts, ROP, congenital glaucoma, refractive error, etc.…”
Section: Discussionmentioning
confidence: 80%
“…The NPB-related eye diseases include congenital cataracts, ROP, congenital glaucoma, refractive error, etc. ROP was identified as the primary cause of neonatal disorders related to vision loss, and the prevalence of blindness due to ROP reached 32% by 2019 ( 22 ). In this study, while the adjusted measurements of SVL and MVL showed an upward trend, blindness displayed a downward trend with a peak around 2010.…”
Section: Discussionmentioning
confidence: 99%
“…ROP is a common avoidable cause of childhood blindness, causing an estimated 32 300 cases of blindness and visual impairment globally in 2010, with the highest incidence in middle-income countries with expanding neonatal care coverage [ 4 ]. In 2022, Zhang et al [ 5 ], based on cause-specific vision loss data from the Global Health Data Exchange, estimated that ROP caused moderate vision loss in approximately 49 100 cases, severe vision loss in 27 500 cases, and blindness in 25 000 cases in 2019 [ 5 ]. The study found that the prevalence of ROP-related blindness varied among 21 Global Burden of Disease regions, with southern sub-Saharan Africa having the highest rate at 44 cases per 100 000 population and East Asia having the lowest rate at 17 cases per 100 000 population [ 5 ].…”
Section: Application Of the Wilson And Jungner Criteria For Ropmentioning
confidence: 99%
“…In 2022, Zhang et al [ 5 ], based on cause-specific vision loss data from the Global Health Data Exchange, estimated that ROP caused moderate vision loss in approximately 49 100 cases, severe vision loss in 27 500 cases, and blindness in 25 000 cases in 2019 [ 5 ]. The study found that the prevalence of ROP-related blindness varied among 21 Global Burden of Disease regions, with southern sub-Saharan Africa having the highest rate at 44 cases per 100 000 population and East Asia having the lowest rate at 17 cases per 100 000 population [ 5 ]. By 2050, estimated global prevalence of moderate, severe vision loss, and blindness caused by ROP is projected to reach 43 600, 23 200, and 31 900 per 100 000 population, respectively [ 5 ].…”
Section: Application Of the Wilson And Jungner Criteria For Ropmentioning
confidence: 99%
See 1 more Smart Citation